Angiotensin II exerts dual actions on sodium-glucose transporter 1-mediated transport in the human jejunal mucosa. (September 2015) - Casselbrant, Anna; Malinauskas, Mantas; Marschall, Hanns-Ulrich; Wallenius, Ville; Fändriks, Lars
Abstract Objectives. Intestinal glucose absorption is mainly mediated via the sodium-glucose transporter 1 (SGLT1) at the apex of the enterocytes, whereas the glucose transporter 2 (GLUT2) provides a basolateral exit. It has been shown in rats that Angiotensin II (AngII), the principal mediator of renin-angiotensin system (RAS), inhibits jejunal SGLT1-mediated glucose absorption. The aim of the present study was to investigate if a similar mechanism exists also in the human jejunal mucosa. Material and methods. Enteroscopy with mucosal biopsy sampling was performed in 28 healthy volunteers. Functional assessments were performed in Ussing chambers using a pharmacological approach. Western blotting and immunohistochemistry were used to assess the presence of the AngII type 1 (AT1R) and type 2 receptor (AT2R), as well as the glucose transporters SGLT1 and GLUT2. Results. Exposure of the mucosa to 10 mM glucose elicited a ≈50% increase in the epithelium-generated current (Iep). This glucose-induced electrogenic response was sensitive to the competitive SGLT1 inhibitor phlorizin, but not to AngII when given alone. AngII combined with the AT2R blocker PD123319 markedly inhibited the response. AngII in combination with the AT1R antagonist losartan tended to increase the electrogenic response, whereas direct activation of AT2R using the agonist C21 significantly enhanced the mucosal response to glucose. The AT1R and AT2R as well as SGLT1 and GLUT2 were detected inside the human enterocytes. Conclusions. The pharmacological analysis indicated that activation of AT1R inhibits, whereas activation of AT2R enhances SGLT1-mediated glucose transport in the human jejunal mucosa.